2015
DOI: 10.1159/000430138
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Cancer Stem Cells from Head and Neck Squamous Cell Carcinoma Cell Lines

Abstract: Background/Aims: Head and neck squamous cell carcinoma (HNSCC) ranks sixth worldwide for tumor-related mortality. A subpopulation of tumor cells, termed cancer stem cells (CSCs), has the ability to support cancer growth. Therefore, profiling CSC-enriched populations could be a reliable tool to study cancer biology. Methods: We performed phenotypic characterization of 7 HNSCC cell lines and evaluated the presence of CSCs. CSCs from Hep-2 cell line and HNSCC primary cultures were enriched through sphere formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 63 publications
(56 reference statements)
3
70
0
1
Order By: Relevance
“…In BMSCC, SOX2 is expressed within the tumor nests, the peritumoral stroma and the endothelium of the microvessels within the peritumoral stroma (29). In OCSCC and oropharyngeal SCC cell lines, SOX2 is overexpressed in CSCs compared to the parental cell population (37). In OTSCC, SOX2 is expressed by cells that also express SALL4, NANOG, phosphorylated STAT3 (pSTAT3), and CD44 (30).…”
Section: Embryonic Stem Cell (Esc) Marker Master Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In BMSCC, SOX2 is expressed within the tumor nests, the peritumoral stroma and the endothelium of the microvessels within the peritumoral stroma (29). In OCSCC and oropharyngeal SCC cell lines, SOX2 is overexpressed in CSCs compared to the parental cell population (37). In OTSCC, SOX2 is expressed by cells that also express SALL4, NANOG, phosphorylated STAT3 (pSTAT3), and CD44 (30).…”
Section: Embryonic Stem Cell (Esc) Marker Master Regulatorsmentioning
confidence: 99%
“…In BMSCC, NANOG is expressed in cells within the tumor nests and the peritumoral stroma (29). In OCSCC and oropharyngeal SCC cell lines, NANOG is overexpressed in the CSC population compared to the parental population (37). Similarly in lip SCC, NANOG is expressed by three distinct putative CSC subpopulations, both within the tumor nests and the peritumoral stroma (42).…”
Section: Embryonic Stem Cell (Esc) Marker Master Regulatorsmentioning
confidence: 99%
“…The bFGF is known to promote the asymmetric division of neural stem cells, which are self-renewable and responsive to EGF. In the presence of EGF, EGF-responsive stem cells are self-replicative to produce secondary bFGF-responsive neural stem cells through mitosis and asymmetric division [8,33,34]. Singh et al isolated sphere cells from neuroepithelial tumor using serum-free culture media [8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tumor stem cells have been identified in colon and liver cancer [33,34]. Selected CD133 + cells, more proliferative than CD133 -cells, could be maintained, which suggested that differentiating tumor cells became apoptotic in the serum-free floating culture supplemented with growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…NNMT expression has been shown to correlate with the migration, invasion, proliferation and survival of cancer cells [16-18]. Over-expression of NNMT in cancer cells resulted in hypomethylated histones by altering the cellular SAM/SAH ratio [19].…”
Section: Introductionmentioning
confidence: 99%